Attitudes and pleasures towards mathematics of discents and their impact on the teaching learning process - Rodríguez, Milagros Elena; Sánchez, Rainier Vicente (Revista Hipótese, 2021)
In the attitudes and likes towards the mathematics of the students and their incidence in the teaching-learning process, the role of the teacher is essential; his own beliefs, attitudes and likes that he has of the process that he directs and imparts or perhaps imposes as the colonial modernist teaching of mathematics. The qualitative-quantitative research analyzes the attitudes and likes of the students of the subject Mathematical logic and set theory of the Bachelor of Mathematics Oriented to Secondary Education, 2020, of the Higher Institute of Teacher Training Salomé Ureña, Dominican Republic. Exit plateaus are given to the unveiled problem.